Molecular Docking, Synthesis, and Tyrosinase Inhibition Activity of Acetophenone Amide: Potential Inhibitor of Melanogenesis. (11th January 2022) - Nazir, Yasir; Rafique, Hummera; Roshan, Sadia; Shamas, Shazia; Ashraf, Zaman; Rafiq, Muhammad; Tahir, Tehreem; Qureshi, Zia-Ur-Rahman; Aslam, Alvina; Asad, Muhammad Hassham Hassan Bin
Abstract : Tyrosinase and its related proteins are responsible for pigmentation disorders, and inhibiting tyrosinase is an established strategy to treat hyperpigmentation. The carbonyl scaffolds can be effective inhibitors of tyrosinase activity, and the fact that both benzoic and cinnamic acids are safe natural substances with such a scaffolded structure, it was speculated that hydroxyl-substituted benzoic and cinnamic acid derivatives may exhibit potent tyrosinase inhibitory activity. These moieties were incorporated into new chemotypes that displayed in vitro inhibitory effect against mushroom tyrosinase with a view to explore antimelanogenic ingredients. The most active compound, 2-((3-acetylphenyl)amino)-2-oxoethyl(E)-3-(2, 4-dihydroxyphenyl)acrylate (5c), inhibited mushroom tyrosinase with an IC50 of 0.0020 ± 0.0002 μ M, while 2-((3-acetylphenyl)amino)-2-oxoethyl 2, 4-dihydroxybenzoate (3c) had an IC50 of 27.35 ± 3.6 μ M in comparison to the positive control arbutin and kojic acid with a tyrosinase inhibitory activity of IC50 of 191.17 ± 5.5 μ M and IC50 of 16.69 ± 2.8 μ M, respectively. Analysis of enzyme kinetics revealed that 5c is a competitive and reversible inhibitor with dissociation constant (Ki) value 0.0072 μ M. In silico docking studies with mushroom tyrosinase (PDB ID 2Y9X) predicted possible binding modes in the enzymatic pocket for these compounds. The orthohydroxyl of the cinnamic acid moiety of 5c is predicted to form hydrogen bond with the active site side chain carbonyl of Asn 260 (2.16 Å) closer to the catalytic site Cu ions. The acetyl carbonyl is picking up another hydrogen bond with Asn 81 (1.90 Å). The inhibitor 5c passed the panassay interference (PAINS) alerts. This study presents the potential of hydroxyl-substituted benzoic and cinnamic acids and could be beneficial for various cosmetic formulations.